An introduction to applied and environmental geophysics - Reynolds, John M. (Wiley-Blackwell, 2011)
"An Introduction to Applied and Environmental Geophysics provides an introduction to the theory and practice of applied geophysics. The book covers a range of applications including mineral and hydrocarbon exploration but the greatest emphasis is on the use of geophysics in civil engineering, and in environmental and groundwater investigations. Since the publication of the 1st edition of An Introduction to Applied and Environmental Geophysics the field of applied and environmental geophysics has grown with significant developments in the subject. The new edition will build on the success of the 1st edition and will include the following key developments: Greater discussion of survey design and standards in geophysical investigations iInclusion of more marine geophysical and geotechical case histories e.g. cable/pipe laying Inclusion of examples of integrated case histories inclusion of new sections dealing with thermal imaging of landfills and radioactivity investigations More information of physio-chemical properties of geological, engineering and environmental materials Greater discussion of borehole techniques especially topography" --